PLURALITY AND DISEMPOWERMENT IN AN ERA OF NEOLIBERAL DEMOCRACY: NIGERIA AND SOUTH AFRICA COMPARED - Onuoha, Godwin (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2018)
This paper draws on the contrasting experiences of Nigeria and South Africa to explore some interesting parallels in the transition to democracy in contemporary Africa. Undoubtedly, several issues have been raised regarding the representative and multi-party democracy in Nigeria and South Africa. This is in view of the fact both countries flaunt their democratic credentials, aspire for continental leadership and possess continental dreams inspired by differing visions that are popular, participatory and inclusive. Yet, Nigeria and South Africa are two of Africa’s most divided countries, and the advent of their respective democratic dispensations indicate that the democracy in place today is initiated in line with a neoliberal agenda, and has so far failed to produce the desired outcomes.